Interventions to support parents of pre-school children with Autism Spectrum Disorders: a systematic review (Research, Society and Development, 2021)
Parents of children with a recently ASD diagnosis face elevated distress and mental health problems like stress, depression, and anxiety. Lately, few interventions which target directly parents of preschool children well-being have been implemented in some researches. It was conducted a review of studies that empirically tested the effects of different kind of interventions targeting improvements in parents of preschool children with ASD well-being. The objective of this review is to find out the different types of interventions that have been used and the outcomes on parental well-being enhancement. Searching on four databases and following a range of search strategies, a total of 9 studies met inclusion criteria. Findings suggest that in most cases, any type of intervention leads to positive effects on parents’ distress and well-being. However, comparisons and conclusions among the different approaches are difficult to be made, as each of the presented studies follows different methodology. Certainly, more studies have to focus on the parents of preschool children with ASD well-being and take into consideration all the limitations of the studies that are reviewed in this paper. Despite this fact, it is very encouraging that more and more researchers and clinicians are concerned about these kinds of interventions in order families with a child with ASD to get supported appropriately.